Analisis Kinerja Likuiditas Koperasi Simpan Pinjam Jaya Utama Berdasarkan Tata Kelola Kas, Piutang, Dan Modal Kerja - Dharma, Budi; Viantika, Dinda Savira; Lestari, Sri (Universitas Labuhanbatu, 2022)
This study makes use of a case study, which is research done directly to gather more precise data, and the outcomes of the research are solely related to the item under examination. To determine the effect of each variable on an individual variable, the data analysis in this study employs dynamic analysis, i.e., analyzing the ratios between accounts contained in the financial statements over multiple periods, also known as cooperative ratio analysis using liquidity ratio analysis. Good management of cash, receivables, and working capital helps maintain cooperative liquidity simultaneously. This is demonstrated by the findings of ratio analysis and the fact that each variable has a substantial effect on cooperative liquidity. In this study, the authors suggest that cooperatives continue to enhance member services and reduce the age of accounts receivable to prevent uncollectible accounts and bad debts.